The mediating role of student–teacher relationships, assertiveness, and curiosity in science achievement - Ramadani, Fehmi; Koliqi, Donika; Pejchinovska-Stojkovikj, Milena; Çibukçiu, Blerina (Frontiers in Education, 2025)
Teacher–student relationships, assertiveness, and curiosity are socio-emotional constructs that influence science achievement. Assertiveness is associated with self-confidence and clear expression, while curiosity fosters exploration and a desire to learn. Investigating their mediating role is important because they represent modifiable factors that teachers and schools can promote to improve science achievement. This study aims to examine the mediating role of student–teacher relationship, assertiveness and curiosity of science achievement. The quality of the student–teacher relationship (RELATST) was assessed through students’ evaluations of seven statements that measured the perceptions of respect and interest from the teachers. Assertiveness (ASSERAGR) measured students’ perceptions through statements indicating self-confidence. The degree of curiosity (CURIOAGR) assessed students’ inclination towards curiosity by evaluating their agreements with statements reflecting a desire to learn and understand, based on data from PISA (2022) in the OECD Report (2024). Whereas PVSCI represents the results achieved in science from testing conducted in the same year. The data were analyzed through the following statistical analysis: confirmatory factorial analysis and second confirmatory factorial analysis, correlation analysis and mediation analysis for the studied variables. The findings reveal that the quality of the student–teacher relationship (QST) has a positive and significant relationship to self-confidence and curiosity, having an indirect impact on achievement in science (PVSCI). QST also has a positive and strong impact on assertiveness (β = 0.176, p < 0.001) and curiosity (β = 0.331, p < 0.001), while assertiveness impacts curiosity (β = 0.239, p < 0.001) which consequently impacts science achievement (β = 0.221, p < 0.001). These results indicate that a good relationship with the teacher fosters the development of the student’s assertiveness and curiosity, which contributes to improving science achievement.